[PP.19.05] PREHYPERTENSION IN EUROPEAN RURAL POPULATION - DATA FROM THE BRISGHELLA HEART STUDY (ITALY) AND ENAH STUDY (CROATIA). (September 2016) - IVKOVIC, V.; Parini, A.; Vrdoljak, A.; Karanovic, S.; Baric, M. Abramovic; Bacchelli, S.; Cagnati, M.; Cicero, A.F.G.; D'Addato, S.; Esposti, D. degli; Fucek, M.; Grandi, E.; et al.
Abstract : Objective: Prevalence of prehypertension (PHT) in various populations is very high. Subjects with PHT have increased cardiovascular (CV) and renal risk and high relative risk of incident (new onset) hypertension (HT). PHT is frequently associated and clustered with multiple CV risk factors. Our aim was to analyse characteristics of subjects with PHT in a cohort of subjects from rural areas in Croatia and Italy. Design and method: In this international prospective long-term follow up study data on 5162 subjects from BrEna cohort formed from original cohorts of Brisighella Heart Study (Italy) and ENAH study (Croatia) were analysed. Out of them, 3306 subjects (1396 m; 1910 w) were eligible for further analyses There were 826 subjects with PHT (391 m, 435w), and 371 of them were followed-up for 109 months (IQR 84–120) and a total of 3120 person-years of follow-up. PHT was defined as BP 120–139/80–89 mmHg. Subjects with diabetes, eGFR<60 ml/min (Cocroft-Gault) and antihypertensive therapy were excluded. Anthropometric and laboratory data as well lifestyle were analysed. Results: PHT prevalence was higher in men than in women (24.99% vs. 28.01%; p<0.001). New-onset or incident HT (NOH) was diagnosed in 214 PHT (57.7%, no between-gender difference) with incidence rate of 6.8% per year; 28.5% of subjects with NOH were treated and 41% controlled. Baseline characteristics of group were: age 48 ± 15, BP 126/78 ± 7/8 mmHg, heart rate 75 (IQR 67–80), BMI 26.4 ± 4.3, waist circumference (WC) 90 ± 12, eGFR 92 (IQR 73–111), FBG 5.1 ± 1, T-chol 5.7 ± 1.2, LDL3.6 ± 1, HDL1.5 ± 0.5, TG1.4 ± 0.8, uric acid 260 ± 90, percentage of overweight (58.3%), obesity (17.7%), visceral obesity (29%), smokers (24.6%) and ex-smokers (18%) who smoked a median of 14 (IQR 6–30) pack-years. Significant predictors of NOH were age, systolic BP and WC (all p < 0.05). At start, those who developed NOH significantly differed from those who remained in PHT category in: age (54 ± 10vs. 46 ± 12), systolic BP (128 ± 7vs. 125 ± 7), WC (91 ± 12vs. 86 ± 12), BMI (26.9 ± 4.2vs. 25.7 ± 3.9), FBG (5.2 ± 0.8vs. 5.0 ± 0.7), LDL-chol (3.8 ± 1.1vs. 3.4 ± 0.9), TG (1.4 ± 0.8vs.1.2 ± 0.7), visceral obesity (34%vs. 21%), overweight (65%vs. 48%) and obesity (22% vs. 14%). Conclusions: Prevalence of PHT in rural European region is high and in line with other reports. High proportion of PHT develop NOH, minority of them are treated and controlled. Obesity and metabolic alterations are frequently present in PHT.